Les expressions verbales figées à l’épreuve de la traduction : Italo Calvino traducteur des Fleurs bleues de Raymond Queneau (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
In this article, we study the choices made by Calvino in his translation of the idiomatic expressions in Raymond Queneau’s Les Fleurs bleues. After briefly sketching the path that led Calvino to take up the challenge of Les expressions verbales figées à l’épreuve de la traduction : Italo Calvino traducteur des Fleurs bleues de Raymond Queneau Mirella Piacentini UNIVERSITÀ DI PADOVA (ITALIA) translating Queneau’s novel, we will study the strategies and techniques that Calvino adopted in translating the idiomatic expressions and attempt to appreciate the impact of these choices on the passage from Les Fleurs bleues to I fiori blu. Our analysis raises the complex question of translational re-creation, all the more crucial when the richness and exuberance of Queneau’s style meets Calvino’s equally rich, surprising and protean style in his capacity as a translator.
Keywords: Les Fleurs bleues, translation, idiomatic expressions, Queneau (Raymond), Calvino (Italo)